BENTUK PENYAJIAN TARI ZAPIN ELANG TETAK KELURAHAN SEDANAU KECAMATAN BUNGURAN BARAT KABUPATEN NATUNA - Ogi Nursauri; Imma Fretisari; Asfar Muniir (Universitas Tanjungpura, 2021)
AbstractThis research is motivated so that complete data and information are documented about the Zapin Elang Tetak Dance both in the form of writing and images and videos of the Zapin Elang Tetak Dance in Sedanau Village, Bunguran Barat Subdistrict, Natuna Regency, because the Zapin Elang Tetak Dance is the first dance in the area. This study uses a descriptive method in a qualitative form and uses a choreographic approach. Sources of data in this research are Mr. Edi Yusuf, Mrs. Fatmawati, and Mr. Nurdin. Data collection techniques in the form of observation, interviews, and documentation. The data validity testing technique used was the extension of the observation and triangulation of sources. Based on data analysis, it is concluded that the form of presentation of Zapin Eagle Tetak Dance in Sedanau Village, Bunguran Barat District, Natuna Regency is as follows. 1. Zapin Elang Tetak Dance tells the story of two eagles who are mating (mating). 2.The Zapin Elang Tetak dance was created to develop the Zapin steps taught by Mr. Ahmad (late) and this dance was created to entertain the local community. 3. The Zapin Elang Tetak dance is danced by the young people as time goes on, this dance is mostly danced by young people. 4. The musical instruments used in the Zapin Elang Tetak Dance are marwas / segmented, tambourine / bebano, gambus / selodang. 5. The clothes used by dancers are in the form of brackets, scarves, buns and flowers, while the musicians wear a telok pot equipped with a skullcap. 6. The stage used by proscenium dancers. 7. The positions used in the Zapin Elang Tetak Dance are not complicated because this dance is a pair dance.Keywords: Presentation Form, Zapin Elang Tetak Dance.